1979
DOI: 10.1002/1097-0142(197904)43:4<1216::aid-cncr2820430409>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of immunologic phenotype of malignant lymphomas by conventional morphology. A study of 60 cases

Abstract: In order to test the immunologic validity of the Lukes-Collins (L-C) classification of the non-Hodgkin's lymphomas (ML), 60 ML in adult patients were studied and their B- or T-cell nature was predicted on a morphologic basis, without knowledge of the clinical history or the results of surface marker (SM) studies (SIg, C', Fc and E-rosettes), which were performed on cell suspensions and cryostat sections from the same specimens used for histology. There was a good correlation between morphologic types and SM (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

1979
1979
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…A recently published review, 4 and a review by our group of the literature indicated that fewer than 100 cases of FL in children have been reported so far. 2,3,[16][17][18][19][20][21] To our knowledge, our analysis represents the largest series of pediatric FL published so far and our cohort can be considered representative for Germany. In addition, all patients in this study were treated similarly within trials of the NHL-BFM group.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published review, 4 and a review by our group of the literature indicated that fewer than 100 cases of FL in children have been reported so far. 2,3,[16][17][18][19][20][21] To our knowledge, our analysis represents the largest series of pediatric FL published so far and our cohort can be considered representative for Germany. In addition, all patients in this study were treated similarly within trials of the NHL-BFM group.…”
Section: Discussionmentioning
confidence: 99%
“…A study of a broader group of unselected lymphomas has found an 8 19'0 predictability of immunophenotype from morphologic features. 45 This would suggest that morphology has different predictive values in the various subtypes of lymphoma and lymphoid leukemias. The finding in the current case of circulating cerebriform (Sezary-like) cells which were B-cells arising from a follicular lymphoma suggests that the predictive value of these cells for T-cell phenotype, although high, should not be regarded as absolute.…”
Section: Discussionmentioning
confidence: 99%
“…9 Vaksin BCG menyebabkan aktivasi 18 Penelitian Albert dkk pada keganasan ovarium, didapatkan kombinasi kemoterapi dengan BCG ternyata dapat meningkatkan remisi dan survival dibandingkan dengan yang hanya mendapat kemoterapi. 19 Penggunaan imunoterapi BCG secara lokal banyak digunakan pada terapi kanker vesica urinaria, yang penggunaannya disuntikkan ke dalam vesica. 10,15 Penelitian Lamm juga mendapatkan pemberian BCG 5 mg secara perkutan setelah reseksi tumor kandung kemih yang dikombinasi dengan radioterapi intravesika, hasilnya menunjukkan interval bebas penyakit dan menurunkan rekurensi.…”
Section: Pembahasanunclassified